Association of HRCT severity score, pre-existing comorbidities, and ABO blood group with treatment outcomes of COVID-19 patients admitted in a hospital of Western Nepal - Dipesh Karki; Saksham K C; Roshani Gurung; Adhikari, Sundar (Asian Journal of Medical Sciences, 2022)
Background: Although many studies have reported the association of different factors with the severity of coronavirus disease (COVID) patients, no concrete scientific conclusions have been reported till date. Aim and Objective: This study aimed to conduct a prospective analysis on different factors associated with the severity and outcome of the COVID-19 patients. Materials and Methods: The study was conducted in a 100-bedded hospital of West Nepal for 3 months, with the total number of hospitalized patients 78. Demographic data, pre-existing comorbidities, ABO blood group, high-resolution computed tomography (CT) severity score, and outcomes of the respondents were recorded and analyzed statistically using Chi-square, binomial regression test, and significance level was considered P<0.05 at 95% confidence intervals. Results: Although the improvement rate was higher among males (84.0%) than females (75.0%), no significant association was observed between sex of the patient and treatment outcomes. Similarly, no significant association was observed in between age and ABO blood grouping of patients and treatment outcome. Furthermore, the chance of improvement is about 6 times higher (OR-6.214, 95% CI: 1.452–26.599; P=0.014) among patients with single comorbidity compared with patients with two or more comorbidities. Moreover, the chance of improvement is 8 times higher (OR-8, 95% CI: 2.034–31.461; P=0.001) in patients with CT severity score 1–15 compared with patients with CT severity score 16–25. Conclusion: CT severity score and pre-existing comorbid conditions play an important role among the different associated factors with the severity and treatment outcomes of COVID-19 patients.